Role of thromboxane-dependent platelet activation in venous thrombosis: Aspirin effects in mouse model. (May 2016) - Tarantino, Eva; Amadio, Patrizia; Squellerio, Isabella; Porro, Benedetta; Sandrini, Leonardo; Turnu, Linda; Cavalca, Viviana; Tremoli, Elena; Barbieri, Silvia S.
Graphical abstract: Abstract: Recent trials suggest that Aspirin (ASA) reduces the incidence of venous thromboembolism in human. However, the molecular mechanisms underlying this effect are still unclear. In this study we assessed the effects of ASA in venous thrombosis mouse model induced by inferior vena cava (IVC) ligation and we investigated the mechanisms responsible for this effect. ASA (3 mg/kg daily for 2 days) treatment decreased the thrombus size, the amounts of tissue factor activity in plasma microvesicles (TF-MP) and the levels of 2, 3-dinor Thromboxane B2 (TXB-M) in urine compared to control mice. Interestingly, the thrombus size positively correlated with both TF-MP activity and TXB-M. In addition, positive correlation was observed between TF-MP activity and TXB-M. A reduced number of neutrophils and monocytes, and of TF-positive cells accompanied to a lower amount of fibrin and neutrophil extracellular traps (NETs) were also found in thrombi of ASA-treated mice. Similar results were obtained when mice were treated 24 h before IVC ligation with SQ29548 (1 mg/kg), a selective thromboxane receptor antagonist. In addition, transfusion of platelets in SQ29548 treated-mice excluded the likelihood of a redundant role of platelet-TP receptor in this context. Finally, incubation of macrophages and neutrophils with SQ29548 prevented TF activity and/or NETs formation induced by supernatant of activated platelets or by IBOP, a selective thromboxane analogue. In conclusion, ASA, suppressing TXA2, prevents macrophages and neutrophils activation and markedly reduces thrombus size with a mechanism most likely dependent of the inhibition of TF activity and NETs formation. These results provide a new link between platelet-produced thromboxane and the occurrence of venous thrombosis.